USE OF ULTRASOUND PROPERTIES IN MEDICINE - Urmanova G. U. (Web of Journals Publishing, 2024)
In the 15th century, Leonardo da Vinci tried to determine the distance between moving ships by submerging a pipe in water. Such experiments eventually led to the development of a means of detecting the sound of underwater objects (sonar) using acoustic radiation. In the 15th century, Leonardo da Vinci tried to determine the distance between moving ships by submerging a pipe in water. Such experiments eventually led to the development of a means of detecting the sound of underwater objects (sonar) using acoustic radiation.
Keywords: Hertz, sound, ultrasound, infrasound, vibrations, waves, acoustics, electroacoustic, membrane.